Association of general and abdominal obesity with age, endocrine and metabolic factors in Asian men - Goh, V.; Hart, William (Informa Healthcare, 2015)
Objective: This study made use of the percent abdominal fat to define abdominal obesity (AbO) and examined the differential associations of general obesity (GOb) and AbO with age, metabolic and endocrine factors. Methods: Metabolic, endocrine and anthropometric factors and body composition were measured in 481 Asian men. Results: A DEXA-derived =25% abdominal fat (PAbdF) was used to define men with AbO. Age was directly associated with PAbdF and percent total body fat (PBF). Exercise intensity was negatively associated with PBF. Both PBF and PAbdF were associated with HDL and LDL, but have opposite correlation with triglyceride. Furthermore, both PBF and PAbdF were associated with the number of metabolic syndrome (MetS) risk factors. Men with GOb had lower levels of percent lean mass (PLM), testosterone and bioavailable testosterone, and higher insulin and glucose levels. Men with AbO had lower arm and leg fat, higher insulin levels and triglycerides. Conclusions: Men with GOb and AbO had different pattern of body composition. Age may be a contributory factor in AbO and a sedentary lifestyle may contribute to GOb. Both GOb and AbO are associated with an increased risk of MetS, with GOb more predispose to risk of diabetes, while AbO more at risk for cardiovascular diseases.